1989
DOI: 10.1111/j.1365-2265.1989.tb01270.x
|View full text |Cite
|
Sign up to set email alerts
|

Virilizing Adrenal Adenoma in an Adult With the Beckwith‐wiedemann Syndrome: Paradoxical Response to Dexamethasone

Abstract: An adult woman with Beckwith-Wiedemann syndrome, hemihypertrophy and an androgen-secreting adrenal adenoma is described. She presented with a 7-year history of progressive virilization and was found to have high plasma levels of testosterone and dehydroepiandrosterone (DHEA) sulphate and elevated levels of urinary metabolites of testosterone and its precursors. Administration of dexamethasone was associated with progressive rises in plasma 17 alpha OH progesterone, 11 beta-desoxycortisol, DHEA sulphate, andros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…They represent only 0.2 % of the cases in the large series studied by Kaltsas et al [29], Azziz et al [30], and Carmina et al [31]. In the cases reported by Clouston et al [11] and Romanelli et al [15], the clinical and hormonal data were similar to the description of our patient, that is, isolated adrenal hyperandrogenism. As recently reported by Keren et al [32], this new case illustrates how SNP array analysis can be useful to overcome the limitations of classical genetic and cytogenetic methods in the diagnosis of BWS.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…They represent only 0.2 % of the cases in the large series studied by Kaltsas et al [29], Azziz et al [30], and Carmina et al [31]. In the cases reported by Clouston et al [11] and Romanelli et al [15], the clinical and hormonal data were similar to the description of our patient, that is, isolated adrenal hyperandrogenism. As recently reported by Keren et al [32], this new case illustrates how SNP array analysis can be useful to overcome the limitations of classical genetic and cytogenetic methods in the diagnosis of BWS.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, 11p15 patUPD is found in about 20 % of BWS patients and is associated with a relatively high tumor risk (10 %). Data concerning cancer risk in adults with BWS are scarce, with only a few tumors reported to date [10][11][12][13][14][15][16]. Whereas complete genome-wide paternal uniparental disomy is lethal in utero causing hydatiform mole, several imprinting disorders are produced by matUPD and patUPD localized to specific chromosomal domains.…”
Section: Genome-wide Paternal Uniparental Disomy As a Cause Of Beckwimentioning
confidence: 96%
“…Greer et al () described a pedigree with CDKN1C mutation responsible for familial BWSp with four adults having fertility issues (azoospermia, low count and motility, abnormal sperm morphology) and hearth anomalies, suggesting echocardiographic follow‐up and semen analysis in adulthood. Other authors reported adults with BWSp and renal anomalies with recurrent urinary tract infections and kidney stones (Clouston et al, ), severe renal function impairment following diffuse nephroblastomatosis and Wilms' tumor (Kulkarni et al, ), hearing deficiency as a consequence of stapedial fixation (Hopsu, Aarnisalo, & Pitkaranta, ), genital anomalies (Aleck & Hadro, ; Clouston et al, ), partial bowel malrotation (Clouston et al, ), pituitary adenoma (Brioude et al, ), long‐QT syndrome (Gurrieri et al, ), psoriasis (Romanelli et al, ), hypothyroidism, and thyroid adenoma (Cardarelli et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little information about the risk for neoplasia in adults. Five adults with BWS who developed neoplasms have been reported—four women with, respectively, an adrenal adenoma [Hayward et al, 1988; Clouston et al, 1989], a basal ganglion astrocytoma [Aleck and Hadro, 1989], bilateral pheochromocytoma [Bémurat et al, 2002], and multiple primaries including thyroid carcinoma and breast cancer [Fleisher et al, 2000]; and one man who developed acute myeloid leukemia [Houtenbos and Ossenkoppele, 2002]. Some of these may be coincidence.…”
Section: Discussionmentioning
confidence: 99%